ANALISIS PENGARUH DIGITAL MARKETING TERHADAP MINAT BELI KONSUMEN DI KICK AVENUE MARKETPLACE - Wijaya, Hendri; Saputra, Suyono (LPPM STIE Muhammadiah Bandung, 2024)
The focus contained in this research is to determine the influence of Price (X1), Perceived Quality (X2), E-wom (X3), Promotion (X4), Trust (X5) and Brand Image (XA) on Purchase Intention (Y) . The research method is quantitative. This research uses smart PLS as the basis for testing. The population in this research is Indonesian people who have an interest in buying Kick Avenue products. In this research, the researcher used 7 variables which were measured with a total of 24 questions, so the total sample required for this research was 24 multiplied by 10, which means the total sample that will be used in this research is 240 Indonesian respondents. The findings can be summarized that the relationship between the variables Price , Perceived Quality , promotion , trust, brand image the Purchase Intention variable has a relevant influence. In contrast to the findings, it can be summarized that the relationship between the E-WOM variables the brand image variable does not have a relevant influence. Compared with the findings in hypothesis VII (Seventh), it can be summarized that the relationship between the E-WOM variables the Purchase Intention variable with brand image mediating does not have a relevant influence.